Fundamentals of fluid mechanics - Munson, Bruce Roy, 1940-; Okiishi, Theodore Hisao, 1939-; Huebsch, Wade W. (Hoboken, New Jersey : John Wiley & Sons, 2009)
Introduction -- Fluid statics -- Elementary fluid dynamics-the bernoulli equation -- Fluid kinematics -- Finite control volume analysis -- Differential analysis of fluid flow -- Dimensional analysis, similitude, and modeling -- Viscous flow in pipes -- Flow over immersed bodies -- Open-channel flow -- Compressible flow -- Turbomachines.
Incluye referencias bibliográficas e índice
Keywords: Mecánica de fluidos; Dinámica de fluidos; Ingeniería hidráulica